Clients of UK healers: A mixed methods survey of their demography, health problems, and experiences of healing. (May 2019) - Rahtz, Emmylou; Child, Sue; Knight, Sue; Warber, Sara L.; Dieppe, Paul
Abstract: Background: Healing has not been well researched, and very little is known about who goes to healers, and what they experience. Methods: A survey of UK-based healers was undertaken with the help of The Confederation of Healing Organisations, asking healers to report on up to 20 consultations. Forms asked about the demography of healer and client, reasons for the consultation, type of healing, and outcomes. Both quantitative and qualitative data were analysed. Results: 278 returned forms from 39 healers (average age 58) were analysed. Healing was described as Spiritual (69%), Reiki (15%) or Energy (10%). The clients had an average age of 57, and 76% were women. The most common reasons for consulting were mental health problems and pain. 93% of the clients reported experiencing immediate benefits. Relaxation, improved wellbeing and relief of pain were often reported. In addition, 76 (27%) had some unusual sensory experiences during the session, such as feelings of warmth, seeing coloured lights, or tingling sensations. The majority of general comments about the experience were positive, and 68% made another appointment. Conclusions: Older people, particularly older women, are the main recipients of healing in the UK, and they go for help with many problems, particularly mental health issues and pain. The majority have a positive experience, and come back for more. In addition to relief of symptoms, many have sensory experiences which could indicate that some special type of interaction was taking place between healer and healee. Highlights: This study explored the experiences of people receiving healing from UK healers (68 characters). Data were obtained from 278 different people, their average age was 57, 76% were female (73 characters). The main reasons for consulting were mental health issues and/or pain; many had multiple health problems (89 characters). 93% reported immediate benefit. Outcomes included relaxation, improved wellbeing and less pain (83 characters). 27% of respondents reported some unusual sensory experience whilst receiving healing (74 characters).